1958
DOI: 10.1139/p58-131
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations on the Dependence of Strain on Stress for Ice

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

1960
1960
1999
1999

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(54 citation statements)
references
References 3 publications
5
49
0
Order By: Relevance
“…suffered from the fact that deformations other than elastic strains were also measured. However, experimental values of 9.9 GN m-2 reported by Gold (1958) and 9.5k0.3 GN m-2 measured by Sinha ( 1978 ) at 233 K for horizontal loading of inclusion free S2 ice provide some support for the theory presented above. Nakaya's ( 1959) data, on the dynamic Young's modulus of ice from a tunnel drilled into the Greenland ice cap, show the modulus to decrease from about 9.2 to 7.5 GN m-2 for a decrease in density from 9 17 to 905 kg m-3.…”
Section: Discussionmentioning
confidence: 64%
“…suffered from the fact that deformations other than elastic strains were also measured. However, experimental values of 9.9 GN m-2 reported by Gold (1958) and 9.5k0.3 GN m-2 measured by Sinha ( 1978 ) at 233 K for horizontal loading of inclusion free S2 ice provide some support for the theory presented above. Nakaya's ( 1959) data, on the dynamic Young's modulus of ice from a tunnel drilled into the Greenland ice cap, show the modulus to decrease from about 9.2 to 7.5 GN m-2 for a decrease in density from 9 17 to 905 kg m-3.…”
Section: Discussionmentioning
confidence: 64%
“…Columnar-grained ice is best characterized as transverse isotropic. Investigations by Gold (1958) showed the relation between strains in the plane of the ice cover to be complex. For example, Poisson's ratio increased from 0.3 to 0.6 as strain increased.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier paper, Gold (1958) presented evidence \vhich indicated that when ice, at a temperature between 0" C and -40" C, is subject to a uniaxial compression normal to the grain boundaries, there is a relaxation of the shear stress at the grain boundaries. Consider the array of hexagonal grains shown in Fig.…”
Section: Discussionmentioning
confidence: 99%